Appropriating the past philosophical perspectives on the practice of archaeology - Scarre, Geoffrey; Coningham, Robin (Cambridge University Press, 2013)
"In this book an international team of archaeologists, philosophers, lawyers, and heritage professionals addresses significant ethical questions about the rights to access, manage, and interpret the material remains of the past. The chapters explore competing claims to interpret and appropriate the past and the major ethical issues associated with them, including handling the sacred; contested rights over sites, antiquities, and artifacts; the involvement of local communities in archaeological research; and the legal status of heritage sites. The book covers a range of hotly debated topics in contemporary archaeological practice, focusing particularly on the relationship between academic archaeologists and indigenous communities for whom the material remnants of the past that form the archaeological record may be part of a living tradition and anchors of social identity"--